Changes in teachers' moral role : from passive observers to moral and democratic leaders - Alt, Dorit; Reingold, Roni (Moral development and citizenship education ;, 2012)
Current Changes in Teacher's Role Definition. From Passive Observer to Moral and Democratic Leader /An Introduction /Dorit Alt and Roni Reingold --Just A Teacher or Also A Moral Example? /Cees Klaassen --Students' Trends and Attitudes on Exam Cheating in Greek Primary and Secondary School Settings /Catherine Dimitriadou, Androniki Gakoudi, Anna Kalaitzidou-Leontaki and Konstantinos Kousaridis --Teachers' Perspectives About Participation at School /Angela Gastager, Jean-Luc Patry and Andrea Wiedemair --Voicing Oppressed Palestinian Women. /Guidelines for Multicultural Literature Curriculum /Lea Baratz and Roni Reingold --Social Literacy Curriculum /Education for Significant Democratic Decision-Making through Integrative Study of Social Problems /Nir Ressissi --School Children's and Adolescents' Tolerance to Contradictions /Towards Democratically Orientated Curriculum Design /Dimitris Pnevmatikos and Eirini Papadopoulou --Multicultural and Democratic Curriculum /History, Problems and Related Metaphors /Nitza Schwabsky --Discovering Virtues with Children /An Experience for an Ethical Curriculum /Luigina Mortari and Valentina Mazzoni --Constructivist Teaching Methods /Can it Promote Civic-Democratic Participation among Adolescents?1 /Dorit Alt --Dialogical and Reflective Activities in The Classrooms to Improve Moral Thinking /Diego Di Masi --Discussion-Based Teaching Methods Addressing Policy Issues Related to Agricultural Biotechnology /Catherine Näpflin, Fritz Oser and Philipp Aerni --Procedural Justice in A Classroom Where Teacher Implements Differentiated Instruction /Dimitris Pnevmatikos and Ioannis Trikkaliotis --Values and Knowledge Education /Experiences with Teacher Trainings /Sieglinde Weyringer, Jean-Luc Patry and Alfred Weinberger --Moral and Democratic Education in The Context of Science Education /What Are the Implications for Teacher Education? /Jostein Saether --Educating Teachers' Ethos /Brigitte Latzko.